Bottom-Up Building of an Innovative Organization: Motivating Employee Intrapreneurship and Scouting and Their Strategic Value. (November 2014) - Park, Soo Hyun; Kim, Jeong-Nam; Krishna, Arunima
This article proposes a theoretical model to understand the ways in which organizations can increase employees' voluntary intrapreneurship and motivated business information seeking and sharing, scouting, via relationship building. Three management strategies—managerial receptiveness to innovative effort, employee empowerment, and communication symmetry—have been tested for their effects on quality of organization–employee relationship (OER), and the effects of OERs on employee's intrapreneurship and scouting. A survey was conducted with 528 employees of organizations that have a minimum of 300 employees in the United States. Results suggest that organizations become innovative and adaptive to the organizational environment as they cultivate relationships with employees because they can motivate employees to engage in voluntary intrapreneurship and scouting in and around the organization.